Rural Supremacy - Shah, Meera (2011)
The success of any brand depends on it acceptance by the consumers. This project highlights the rural buying behaviour. The rural consumers tend to show a closed mind towards branded goods and services. Though the current scenario is improved than the past but still large amount of rural market is untapped. The marketers now understand the potential at the bottom of the pyramid but there are doubts regarding the way this market can be reached and converted into customers. Many factors like income, education, media exposure, taste and preference etc, play an important role in driving the buying behaviour of the rural population. Often companies face problems in succeeding in the rural market, although they might have a good record in the urban market. This is because few companies fail to understand the difference between the urban market and the rural market. The marketing strategies adopted for the urban market cannot be used for the rural market also as it is a completely different mindset that is to be dealt with. However many big multinationals have now realized this need and have emerged with strategies specific to the rural market. For instance brands like Colgate, Lux, Coca Cola are few of the highest selling in the rural market. Through this project it is aimed to understand the reluctance consumers show towards branded products and for this purpose the case study of the company ‘ Everest Spices is used. The research is specifically based on the acceptance of branded spices in the rural market compared to the homemade spices which has been an age old tradition